(untitled) (Journal of the College of Basic Education, 2022)
Developed countries are competing to create new urban areas and expand the old to accommodate this huge increase, as a class of the most innovative and daring architects emerged in designing their ideas for future cities. One place is one of the aspects in which big data has been used and achieved great success, and on this basis many developed countries in the world seek to implement the concept of smart cities, which are cities that have digital technology integrated across all city functions. Future cities use technology extensively in all aspects of life With the growing use of touch screens and smart phones, this will not be difficult, as the GPS will be widely used in the city so that no one will get lost after that, using smart screens, the person finds the easy direction to reach the location he wants to go To him, and if the motorists in the current cities suffer in parking them in a place that may take them a lot of time due to congestion, the electronic sensors in the cities of For a future, as well as the proliferation of smart and small cars, and electronic applications through which it can easily find a place, as it is possible to spread small-sized aircraft for civilian use as an alternative to cars, the climate will be more controlled so that cities are covered with a transparent plasma cover or envelope like envelope Atmosphere to allow the weather to be controlled and perhaps the climate will be controlled more so that the cities will be covered with a transparent plasma cover or an envelope like the atmosphere and huge machines on the outskirts of the city that control the temperature and the strength of the desired brightness of the sun and generate winds or allow them to pass after filtering and filtering from all the harmful substances coming from outside. In any case, all of the above, some of them are implemented and others are still plans for the future